2006
DOI: 10.1177/10883576060210020301
|View full text |Cite
|
Sign up to set email alerts
|

Are the Majority of Children With Autism Mentally Retarded?

Abstract: There are frequent claims in the literature that a majority of children with autism are mentally retarded (MR). The present study examined the evidence used as the basis for these claims, reviewing 215 articles published between 1937 and 2003. Results indicated 74% of the claims came from nonempirical sources, 53% of which never traced back to empirical data. Most empirical evidence for the claims was published 25 to 45 years ago and was often obtained utilizing developmental or adaptive scales rather than mea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
3
3
3

Relationship

0
9

Authors

Journals

citations
Cited by 92 publications
(10 citation statements)
references
References 51 publications
0
8
0
Order By: Relevance
“…Along this line, a meta-study evaluating 215 research articles published between 1937 and 2003 with claims about mental retardation found that 74% of these claims came from non-empirical sources, of which 53% were never traced back to empirical data. Astonishingly, most of the empirical evidence was published 25–45 years ago and based on measures of development rather than tests of intelligence or cognitive capabilities (Goldberg Edelson, 2006 ). But even when autistic intelligence is tested with approved intelligence tests it is necessary to interpret the results with caution.…”
Section: Support Contradictions and Unificationmentioning
confidence: 99%
“…Along this line, a meta-study evaluating 215 research articles published between 1937 and 2003 with claims about mental retardation found that 74% of these claims came from non-empirical sources, of which 53% were never traced back to empirical data. Astonishingly, most of the empirical evidence was published 25–45 years ago and based on measures of development rather than tests of intelligence or cognitive capabilities (Goldberg Edelson, 2006 ). But even when autistic intelligence is tested with approved intelligence tests it is necessary to interpret the results with caution.…”
Section: Support Contradictions and Unificationmentioning
confidence: 99%
“…ID is heavily represented in a wide range of neurodevelopmental disorders (NDD), including Down syndrome (DS), fetal alcohol syndrome, autism spectrum disorder (ASD), tuberous sclerosis, fragile X syndrome (FXS), Rett syndrome, and many other genetic conditions and syndromes with a spectrum of etiologies yet to be identified (idiopathic ID). In ASD, estimated to affect 1 in 88 children by the Centers for Disease Control (CDC), a meta-analysis of studies revealed a rate of ID as high as 75 % [1]; although more recent large-scale epidemiological studies reflect a rate of approximately 41 %.…”
Section: Introductionmentioning
confidence: 99%
“…Over the years, criticism about the use of IQ assessments for children with developmental disabilities, when compared to other methods of assessment, have mounted. For instance, in a systematic review, spanning over six decades, a prevalence rate of 75% intellectual disability in ASD, was reported [8]. Edelson, the author of this review pointed out that the prevalence rate of intellectual disability in ASD varied as a function of the testing method used in the study.…”
Section: Iq As An Assessment Measurementioning
confidence: 99%